Analisis Media untuk Tujuan Edukasi Konsumsi Buah dan Sayuran bagi Anak Usia Dini - Maulani, Meisri Savitri; Retnoningsih, Sri (Visualita Jurnal Online Desain Komunikasi Visual, 2025)
The high level of junk food consumption compared to eating fruits and vegetables can increase obesity rates in Indonesia, especially if the habit is carried out from an early age. Education from an early age about the importance of eating fruits and vegetables is needed so that children's nutritional needs are met and their growth and development are balanced. This study was conducted to find a suitable solution so that children can be interested in learning about the importance of fruits and vegetables, and also to get used to starting to consume them. By analyzing how children behave in dealing with fruits and vegetables, we also look for solutions to deal with them. This study was also conducted to be able to compare what learning media are effective in educating early childhood. Using a mixed research methodology between quantitative and qualitative. Data collection through literacy studies and also using interviews with one of the principals in the city of Bandung and distributing questionnaires to parents of children. The approach through children's illustrated books as a learning medium can be used to increase children's interest in literacy and also in fruits and vegetables.